Hadith #1046 - Sahih Muslim - al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان (Sahih Muslim)
You have made us equal to the dogs and the asses, whereas I lay on the bedstead and the Messenger of Allah (ﷺ) came there and stood in the middle of the bedstead and said prayer. I did not like to take off the quilt from me (in that state), so I moved away quietly from the front legs of the bedstead and thus came out of the quilt.
Grade: Sahih

Hadith #2463 - Sahih Muslim - al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان (Sahih Muslim)
I and Masruq went to ‘A’isha (Allah be pleased with her) and asked. her if the Messenger of Allah (ﷺ) embraced (his wives) while fasting. She said: Yes; but he had the greatest control over his desire among you: or he was one of those who had control over his desire.
Grade: Sahih

Hadith #4524 - Sahih Muslim - al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان (Sahih Muslim)
The Messenger of Allah (ﷺ) was in a cave (or raid) when his finger was hurt.
Grade: Sahih

Hadith #4525 - Sahih Muslim - al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان (Sahih Muslim)
” Wa’dd hd wa’l-laili iza saja, ma wadda’ka Rabbuka wa’ ma qala” .
Grade: Sahih

Hadith #4526 - Sahih Muslim - al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان (Sahih Muslim)
I heard Jundub b. Sufyan say: The Messenger of Allah (ﷺ) fell ill and did not wake up for two or three nights (for prayers) A woman came to him and said: Muhammad, I hope that your satan has left you. I haven’t seen him approach you for two or three nights. The narrator says: At this, Allah, the Glorious and Exalted, revealed:” By the Glorious……”
Grade: Sahih

Hadith #6399 - Sahih Muslim - al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان (Sahih Muslim)
What makes you laugh? They said: Such and such person stumbled against the rope of the tent and he was about to break his neck or lose his eyes. She said: Don’t laugh for I heard Allah’s Messenger (ﷺ) as saying: If a Muslim runs a thorn or (gets into trouble) severe than this, there is assured for him (a higher) rank and his sins are obliterated.
Grade: Sahih